Optimizing Adjuvant Care in Early Breast Cancer: Multidisciplinary Strategies and Innovative Models from Canadian Centers - Angela Chan; Nancy Nixon; Muna Al-Khaifi; Alain Bestavros; Christine Blyth; Winson Y. Cheung; Caroline Hamm; Thomas Joly-Mischlich; Mita Manna; Tom McFarlane; Laura V. Minard; Sarah Naujokaitis; et al. (Current Oncology, 2025)
The adjuvant treatment landscape for hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2–) early breast cancer (EBC) is rapidly evolving, with a diverse range of therapeutic options—including endocrine therapies, bisphosphonates, ovarian function suppression, olaparib, CDK4/6 inhibitors, and emerging agents such as immunotherapy. While these advances have markedly improved patient outcomes, they also introduce challenges related to implementation, monitoring, and resource allocation. Notably, therapies like CDK4/6 inhibitors require particularly close monitoring, creating logistical and capacity challenges for medical oncologists, whose workloads are already stretched due to rising cancer incidence and treatment complexities. These challenges underscore the need for innovative care delivery solutions to ensure patients with EBC continue to receive optimal care. This paper offers a comprehensive guide—a playbook—of multidisciplinary-team-based care models designed to optimize adjuvant treatment delivery in EBC. Drawing on real-world evidence and successful applications across Canadian centers, we explore models led by nurses, nurse practitioners (NPs), general practitioners in oncology (GPO), and pharmacists. Each model leverages the unique expertise of its team to manage treatment toxicities, facilitate adherence, and enhance patient education, thereby promoting effective and sustainable care delivery. Importantly, these models are not intended to compete with one another, but rather to serve as a flexible recipe book from which breast cancer care teams can draw strategies tailored to their local resources and patient needs. By detailing implementation strategies, benefits, and challenges—in many instances supported by quantitative metrics and economic evaluations—this work aims to inspire care teams nationwide to optimize the adjuvant management of patients with HR+, HER2– EBC.